Rift : a memoir of breaking away from Christian patriarchy - West, Cait, 1988- (William B. Eerdmans Publishing Company, 2024)
"Cait West's memoir shares her upbringing as a stay-at-home daughter and her eventual escape from Christian patriarchy"--